Janusz Nagórny’s Interpretation of the Personalistic Category of Participation and Its Implementation in the Theological-Moral Reflection on Social Life - Tadeusz Zadykowicz (Verbum Vitae)
Moral theology, like any science, develops not only through the addition of new concepts but also through the explanation of phenomena with increasing accuracy and depth by applying adequate tools and methods, which can and should be improved. In describing the essence of social life and morally evaluating social attitudes, such a tool is provided by the personalistic category of participation. This category – extensively discussed by Karol Wojtyła in his book The Acting Person – was originally interpreted and applied to the theological-moral reflection on social life by Fr. Janusz Nagórny (1950–2006) – moral theologian from the John Paul II Catholic University of Lublin. What was his contribution to this implementation? What rendered his understanding of participation so original? What were the methodological and substantive consequences of such a reception? To answer these questions, the author analyses Nagórny’s publications, including those which so far – mainly due to their popular science and popularising character – have not been the subject of more in-depth study. The analysis presented here leads to the conclusion that Nagórny lent a theological character to a philosophical category by its biblification and, in such an interpretation, he applied it to detailed areas of social life. Furthermore, the use of elements of the historical method justifies the thesis that he was the initiator of this type of implementation and contributed to making it popular in Polish moral theology.